2021
DOI: 10.1111/acel.13291
|View full text |Cite
|
Sign up to set email alerts
|

α‐ketoglutarate delays age‐related fertility decline in mammals

Abstract: The fecundity reduction with aging is referred as the reproductive aging which comes earlier than that of chronological aging. Since humans have postponed their childbearing age, to prolong the reproductive age becomes urgent agenda for reproductive biologists. In the current study, we examined the potential associations of α‐ketoglutarate (α‐KG) and reproductive aging in mammals including mice, swine, and humans. There is a clear tendency of reduced α‐KG level with aging in the follicle fluids of human. To ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 44 publications
(57 reference statements)
1
28
0
Order By: Relevance
“…We also identified a number of glucose derivatives and tricarboxylic acid (TCA) cycle intermediates or derivatives as well as fatty acids, the steroid ester cholesterol sulfate, and the nucleoside uridine. The majority of the metabolites identified in this study have been previously identified in the follicular fluid of cattle, humans, pigs, sheep, and horses [ 26 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. To our knowledge, the metabolites N-acetyl-beta-alanine, O -acetyl-l-serine, 2-oxo-4-methylthiobutanoate, 3-methylphenylacetic acid, phenyllactic acid, N-acetylornithine, tricarbalylic acid, 2-dehydro-D-gluconate, and D-gluconate are more novel components of the mammalian follicular fluid metabolome.…”
Section: Resultsmentioning
confidence: 99%
“…We also identified a number of glucose derivatives and tricarboxylic acid (TCA) cycle intermediates or derivatives as well as fatty acids, the steroid ester cholesterol sulfate, and the nucleoside uridine. The majority of the metabolites identified in this study have been previously identified in the follicular fluid of cattle, humans, pigs, sheep, and horses [ 26 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. To our knowledge, the metabolites N-acetyl-beta-alanine, O -acetyl-l-serine, 2-oxo-4-methylthiobutanoate, 3-methylphenylacetic acid, phenyllactic acid, N-acetylornithine, tricarbalylic acid, 2-dehydro-D-gluconate, and D-gluconate are more novel components of the mammalian follicular fluid metabolome.…”
Section: Resultsmentioning
confidence: 99%
“…AKG is an important intermediate in the TCA cycle, impacts ATP production as a key point in the anaplerotic pathway [ 7 , 15 , 46 , 47 ], involved in the biosynthesis of proteins and amino acids [ 48 ] as a substrate of amino acid transferase and glutamate dehydrogenase, and influences epigenetic regulation in ageing [ 7 , 19 , 20 ]and metabolism [ 8 , 49 ] as an obligate substrate of histone and DNA demethylases [ 15 , 50 ]. Exogenous AKG also affects the cellular energy supply under the effects of various adverse factors [ 14 , [51] , [52] , [53] ], such as bacterial endotoxins and hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…AKG is an essential cofactor and substrate for many biological enzymes, including hypoxia-inducible factor (HIF) prolyl hydroxylases (PHDs) and the histone demethylases JMJDs and ten-eleven translocation hydroxylases (TET1-3), which are involved in DNA demethylation [ 15 ], and participates in multiple cellular metabolic and regulatory pathways. Growing evidence suggests that AKG has protective effects, such as its ability to regulate metabolism [ 16 ], promote autophagy [ 17 ], reduce inflammation [ 18 ], delay ageing [ 19 , 20 ] and extend life span [ 21 ]. Although previous studies showed the association between a high circulating AKG level with HF severity and short-term adverse outcome in HF patients, there have been fewer relevant studies on the effects of AKG in HF.…”
Section: Introductionmentioning
confidence: 99%
“…The study demonstrates the importance of α-KG on reproductive aging in mammals including mice, pigs, and humans [43], and we think α-KG supplementation improves meiotic maturation of porcine oocytes and promotes the development of PA embryos by activating cellular antioxidant response mechanisms.…”
Section: Discussionmentioning
confidence: 61%